Prendre en compte la vulnérabilité dans la répartition mondiale des financements concessionnels - Patrick Guillaumont (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
– In the run-up to the Paris Summit, the question of mobilizing new resources to finance development and global public goods seems to receive much more attention than the way in which these new funds, like the old ones, are allocated among countries. If there is to be a "financial pact", it should be with countries, for whom allocation is crucial. Some priority is to be given to countries that are vulnerable to varying degrees to exogenous shocks, external or natural.
Keywords: 330; Least developed Countries (LDCs); Vulnerabilities